The life of George Eliot : a critical biography - Henry, Nancy, 1965- (Blackwell critical biographies., 2012)
The life story of the Victorian novelist George Eliot is as dramatic and complex as her best plots. This new assessment of her life and work combines recent biographical research with penetrating literary criticism, resulting in revealing new interpretations of her literary work. A fresh look at George Eliot's captivating life storyIncludes original new analysis of her writingDeploys the latest biographical researchCombines literary criticism with biographical narrative to offer a rounded perspective.